Astaxanthin mitigates cobalt cytotoxicity in the MG-63 cells by modulating the oxidative stress - Dahe Li; Wenwen Tong; Denghui Liu; Yuming Zou; Chen Zhang; Weidong Xu (BMC, 2017)
Abstract Background With the re-popularity of metal-on-metal (MoM) bearing in recent years, the cobalt toxicity has been a cause for concern in the total hip replacement surgery by both physicians and patients. Methods MG-63 cell line was cultured in vitro and incubated with cobalt (II) chloride (CoCl2) and/or with astaxanthin (ASX) for 24 h. MTT assay was conducted to evaluate the cell viability after cobalt exposure and ASX treatment. Fluorescence-activated cell sorting (FACS) analysis was performed to examine the reactive oxygen species (ROS) level. Quantitative real-time polymerase chain reaction (PCR) was adopted to determine the mRNA levels of related targets. And western blot analysis was used to examine the protein expressions. One-way ANOVA with posttest Newman-Keuls multiple comparisons was adopted to analysis all the obtained data. Results In the current study, ASX exhibited significant protective effect against the Co(II)-induced cytotoxicity in MG-63 cell line. We also found that ASX protected the cells against Co-induced apoptosis by regulating the expression of Bcl-2 family proteins. Besides, heme oxygenase 1 (HO-1) could be activated by Co exposure; ASX treatment significantly inhibited HO-1 activation, suppressing the oxidative stress induced by Co exposure. Moreover, c-Jun N-terminal Kinase (JNK) phosphorylation was shown to participate in the signaling pathway of the protective effect of ASX. However, knockdown of JNK expression by siRNA transfection or JNK inhibitor SP600125 treatment did not affect the protective effect of ASX against cobalt cytotoxicity in MG-63 cells. Conclusions ASX mitigated cobalt cytotoxicity in the MG-63 cells by modulating the oxidative stress. And ASX could be a promising therapy against cobalt toxicity in the hip articulation surgery.